Taking stock of the status of implementation of the Voluntary Guidelines for Securing Sustainable Small-scale Fisheries: A country-level assessment framework. (February 2019) - Courtney, Catherine A.; Pomeroy, Robert; Brooks, Stephen H.
Abstract: With the growing recognition of the significance of small-scale fisheries, the FAO working member states developed the Voluntary Guidelines on Securing Sustainable Small-Scale Fisheries in the Context of Food Security and Poverty Eradication (SSF Guidelines). In order to increase awareness and catalyze the uptake of the guidelines by national governments, a simpler framework and process was developed and tested in two countries for use by governments to assess their progress in meeting the guidelines. These SSF Guidelines were re-structured into an assessment framework to enable a country-level assessment of the status of implementation and to inform development programming and project design. The assessment process consisted of a combination of desk reviews, expert consultations, and workshops. The SSF assessment framework and process provides a step forward to increase awareness and application of the SSF Guidelines in support of sustainable small-scale fisheries. Highlights: Need for a simpler process for governments to assess progress in meeting FAO SSF Guidelines. Assessment framework to enable a country-level assessment of the status of FAO SSF Guidelines. Assessment framework is a step forward to raise awareness and application of FAO SSF Guidelines.